Enantioselective Total Synthesis of the Putative Biosynthetic Intermediate Ambruticin J - Trentadue, Kathryn (Chemistry, 2021)
The family of anti-fungal natural products known as the ambruticins are structurally distinguished by a pair of pyran rings adorning a divinylcyclopropane core. Previous characterization of their biosynthesis, including the expression of a genetically modified producing organism, revealed that the polyketide synthase pathway proceeds through a diol intermediate, known as ambruticin J. Here we report the first enantioselective total synthesis of the putative PKS product, ambruticin J, via a triply-convergent synthetic route featuring a Suzuki-Miyaura cross-coupling and a Julia-Kocienski olefination for fragment assembly. This synthesis takes advantage of synthetic methodology, previously developed by our laboratory, for the stereoselective generation of the trisubstituted cyclopropyl linchpin.